UNVEILING GENDER BIAS THROUGH CRITICAL DISCOURSE ANALYSIS: REPRESENTATION IN ENGLISH FOR NUSANTARA MERDEKA CURRICULUM TEXTBOOK - Andi Robby Samawa; Iwan Jazadi (STKIP Paracendekia NW Sumbawa, 2025)
This study critically examines gender representation in the English for Nusantara Grade VII textbook, the flagship English Language Teaching (ELT) material for Indonesia’s Merdeka Curriculum. Using a qualitative design and Fairclough’s three-dimensional Critical Discourse Analysis (CDA), twelve multimodal extracts from Chapter 1 were analyzed to uncover how male and female identities are portrayed through text and visuals. The findings reveal a clear imbalance in both frequency and agency: male characters appear nearly three times more often than female characters and are consistently depicted as active protagonists with hobbies and social interactions, while female figures are limited to passive or relational roles, such as sisters or unnamed peers. Despite the curriculum’s stated goal of inclusivity and gender equity, the textbook subtly reproduces patriarchal ideologies and hegemonic masculinity through muted female voices and restricted social positioning. These results echo global patterns of gender bias in ELT materials and highlight a critical gap between policy aspirations and classroom realities. The study concludes by offering practical implications for teachers, textbook authors, and policymakers, emphasizing the need for gender-sensitive material development and critical literacy approaches in ELT classrooms